Modern Technologies and Their Influence in Fermentation Quality - Benito, Santiago (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
During the last few years, industrial fermentation technologies have advanced in order to improve the quality of the final product. Some examples of those modern technologies are the biotechnology developments of microbial materials, such as Saccharomyces and non-Saccharomyces yeasts or lactic bacteria from different genera. Other technologies are related to the use of additives and adjuvants, such as nutrients, enzymes, fining agents, or preservatives and their management, which directly influence the quality and reduce the risks in final fermentation products. Other technologies are based on the management of thermal treatments, filtrations, pressure applications, ultrasounds, UV, and so on, which have also led to improvements in fermentation quality in recent years. The aim of the issue is to study new technologies able to improve the quality parameters of fermentation products, such as aroma, color, turbidity, acidity, or any other parameters related to improving sensory perception by the consumers. Food safety parameters are also included.